Aspectos clínicos do periodonto de mulheres e sua associação com a gravidez - CALADO, Keiko Aramaki Abreu (2021)
Introduction: Hormonal changes that occur during pregnancy can induce an immune response to dental biofilm and cause vascular and gingival changes that may contribute to increased gingival inflammation. In addition, periodontitis can play the role of a distant reservoir of microorganisms and inflammatory mediators, thus contributing to the occurrence of adverse events in pregnancy. The aim of this study was to analyze the clinical aspects of the periodontal in women and verify its association with pregnancy. Methods: This is an analytical cross- sectional observational study with the participation of 40 participants divided into 2 groups (n=20): 20 women in immediate postpartum period and 20 women who never became pregnant. Participants were submitted to socioeconomic and harmful habits and oral hygiene questionnaires. In addition, a clinical periodontal examination in the whole mouth was performed in all participants, to obtain the following parameters: probing depth (PD), gingival bleeding index (GBI) and level of clinical attachment (LCA). Categorical variables were analyzed using Fisher's Exact and G Williams tests. In numerical variables, the Shapiro-Wilk test was used to measure the normality of the distribution and, later, the Mann Whitney U statistical test was used to verify the association between the study groups and the clinical periodontal parameters. The significance level adopted for all statistical tests was 5%. Results: The mothers were predominantly black/brown (75%), 55% did not work, 95% had a partner, 90% had completed elementary/high school, 70% had lower family income, 40% reported brushing their teeth twice a day, 60% did not floss and 80% did not visit the dentist in the last year. While in the group of women who never became pregnant, white skin color was more common (65%), 75% had completed higher education, 80% were single, 70% brushed their teeth 3 times a day, 85% used the floss dental care and among these 65% used it at least once a day and 60% visited the dentist in the last year. There were statistically significant differences regarding skin color (p = 0.0248), education (p = 0.0001), monthly family income (p = 0.0036), marital status (p < 0.0001), visit to the dentist in the last year (p = 0.0128), flossing (p=0.0079) and its daily frequency (p < 0.0001), alcohol use (p= 0.0008), gingival bleeding index (p=0.0339), number of sites with LCA≥3mm (p =0.0072) and number of teeth (p=0.0024). Conclusion: The postpartum women showed a lower socioeconomic level, lower education than the group of women who never got pregnant, and poorer oral hygiene practices. In addition, they had a higher rate of gingival bleeding, a greater number of sites with attachment loss, and a smaller number of teeth in the oral cavity.